The Clash of Empires in Africa: The First World War in the British and German Colonies - Steinbach, Daniel (Trinity College Dublin, 2007)
From its very beginnings the First World War was a global war. The most severe fighting outside Europe took place in the tropical German colonies of the Cameroons and German East Africa (present-day Tanzania), as well as in the deserts of German Southwest Africa (present-day Namibia). The main burden of the war was carried on the shoulders of the Africans who either were enlisted as regular soldiers or forced into service as porters and servants. Although the Europeans relied on the solidarity of 'all whites in Africa' in order to uphold the colonial regime, hundreds of British and German civilians volunteered to defend the 'outpost of the Empire' or 'the new homeland' against 'the brutal Huns' or 'the greedy English'. The aim of this research project is to highlight the perception, experience, and consequences of the First World War among these European colonials and their reaction, rationalisation and mystification of a war which potentially threatened their economic and social supremacy.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: German Colonies; British Colonies; First World War